Simultaneous Determination of Nitrate and Nitrite in Wrapper by High-Performance Liquid Chromatography with Cloud-Point Extraction - Li, Xiaolan; Meng, Dongling; Zhao, Jiao; Yang, Yaling (Asian Journal of Chemistry, 2014)
A simple, fast, sensitive and accurate reversed-phase HPLC methodology for simultaneous monitoring of nitrate and nitrite in wrapper is described. Nitrite was determined directly using the Griess diazo-coupling reaction and the formed azo dye was measured at 510 nm by HPLC with cloud point extraction. Nitrate based on the ion pair chromatography to be quantified by HPLC when UV light absorption responses at 210 nm. Ultrasonic-assisted extraction was utilized to reduce extraction time and improve extraction efficiency when nitrate and nitrite were extracted from the paper. The effective parameters of the extraction process such as ultrasonic auxiliary extraction time, the volume of nonionic surfactant (Triton X-114), sample pH, ionic strength, equilibration temperature and time were optimized. Under the optimum conditions, this method was characterized by an acceptable linear range of 5 to 800 ng/mL for nitrite, 0.1 to 10 μg/mL for nitrate and correlation coefficients of the calibration curves were both higher than 0.996. The limits of detection are 5 ng/mL and 100 ng/mL for nitrite and nitrate respectively. The proposed method was successfully applied to the extraction and determination of nitrite and nitrate in wrapper and the satisfactory relative recoveries (86.1-96.6 %) were obtained.